AI-Enhanced Learning Experiences: Moving Beyond Traditional Textbook Approaches in Global Education - Munawwaroh, Izzatul; Adeleke Adeoye, Moses (Educative: Jurnal Ilmiah Pendidikan, 2024)
This study aims to explore how AI (artificial intelligence) can transform the learning experience by going beyond the limitations of traditional textbook-based methods in global education. With a qualitative research approach and case study type, data were collected through semi-structured interviews and participant observations at Madrasah Aliyah Nurul Jadid Paiton Probolinggo, which has implemented AI technology, and through documentation analysis. The study results show that data-based learning allows teachers to design more personalized and effective learning through comprehensive data analysis. Meanwhile, automated teaching through AI provides real-time guidance and feedback, accelerating students' understanding of the subject matter. These findings indicate that integrating AI in madrasah education improves the quality of learning and creates a more inclusive and adaptive learning environment.